Characterizing Relationship of Microbial Diversity and Metabolite in Sichuan Xiaoqu - Tang, Qiuxiang; He, Guiqiang; Huang, Jun; Wu, Chongde; Jin, Yao; Zhou, Rongqing (Frontiers in Microbiology, 2019)
Xiaoqu is a fermentation starter used in the production of Xiaoqu jiu which is also one of traditional Chinese liquor. The quality and microbial community characteristics of Xiaoqu was closely related with the yield and flavor feature of fresh Xiaoqu jiu. Present study aimed to explore the mystery behind microbial diversity and volatiles of Xiaoqu by polyphasic detection methods such as Illumina MiSeq platform and metabolites analyzing method. Results showed that the difference of the microbial community diversity among samples was significant. The hydrolytic ability was positively correlated with α- and β-diversity of bacteria, but was negatively correlated with that for fungi. Staphylococcus and Weissella were dominant bacteria, while the dominant fungi were Rhizopus and Candida, the abundance ranged from 33.66% to 91.53% for the former, while were 58.51% and 48.72%, respectively in sample No3 and sample No4, respectively, for the latter. The difference of microbial community diversity resulted in the discrepancy of volatile profile and interaction relationship among genus. 24 dominant bacteria and 7 dominant fungi were correlated with 20 different volatiles. This study provided a scientific perspective for the uniformity and stability of Xiaoqu jiu and might aid in controlling the manufacturing process.